The Rationale for Exercise in the Management of Pain in Parkinson’s Disease - Allen, Natalie E. (J Parkinsons Dis, 2015)
Pain is a distressing non-motor symptom experienced by up to 85% of people with Parkinson’s disease (PD), yet it is often untreated. This pain is likely to be influenced by many factors, including the disease process, PD impairments as well as co-existing musculoskeletal and/or neuropathic pain conditions. Expert opinion recommends that exercise is included as one component of pain management programs; however, the effect of exercise on pain in this population is unclear. This review presents evidence describing the potential influence of exercise on the pain-related pathophysiological processes present in PD. Emerging evidence from both animal and human studies suggests that exercise might contribute to neuroplasticity and neuro-restoration by increasing brain neurotrophic factors, synaptic strength and angiogenesis, as well as stimulating neurogenesis and improving metabolism and the immune response. These changes may be beneficial in improving the central processing of pain. There is also evidence that exercise can activate both the dopaminergic and non-dopaminergic pain inhibitory pathways, suggesting that exercise may help to modulate the experience of pain in PD. Whilst clinical data on the effects of exercise for pain relief in people with PD are scarce, and are urgently needed, preliminary guidelines are presented for exercise prescription for the management of central neuropathic, peripheral neuropathic and musculoskeletal pain in PD.